The Role and Status of Women in Mesopotamian Historical Discourse: A Study of Myths and Epics - Habeeb Obaid, Assist. Lect. Hassan; Hashem Ali, Prof. Dr. Adel (Basra studies journal, 2025)
Women held a distinguished status and high esteem in ancient Iraqi society. Literary works, particularly myths and epics, offer significant historical insights through the discourse of ancient Mesopotamian scribes, highlighting the prominent role of women in prehistoric times. They were depicted as nurturing mothers and fertile lands, generously sustaining society. Women played a pivotal and influential role, earning reverence and even worship as life-giving and fertility-endowing figures. They were also regarded as creators, leading to the recognition of that era as a matriarchal society. However, these texts also reveal a decline in women's role over time, as men gradually assumed dominance. This shift might be attributed to changing cultural norms, evolving societal attitudes, or men’s realization of their capabilities in ascending the social hierarchy. Despite this, women did not completely retreat from prominence; instead, they became essential supporters, complementing men’s roles and continuing to contribute significantly to society.